Traditional Chinese Medicine Tanreqing Targets Both Cell Division and Virulence in Staphylococcus aureus - Yang, Weifeng; Cui, Kaiyu; Tong, Qian; Ma, Shuhua; Sun, Yanan; He, Gaiying; Li, Dongying; Lin, Longfei; Blazekovic, Biljana; Chevalier, Sylvie; Wang, Yuanhong; Wei, Qing; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Staphylococcus aureus has been recognized as an important human pathogen and poses a serious health threat worldwide. With the advent of antibiotic resistance, such as the increased number of methicillin-resistant Staphylococcus aureus (MRSA), there is an urgent need to develop new therapeutical agents. In this study, Chinese traditional medicine Tanreqing (TRQ) has been used as an alternative treating agent against MRSA and we aim to unravel the mode of action of TRQ underlying MRSA inhibition. TRQ treatment affected numerous gene expression as revealed by RNA-seq analysis. Meanwhile, TRQ targeted cell division to inhibit cell growth as shown by illumination microscopy. Besides, we confirmed that TRQ downregulates the expression of virulence factors such as hemolysin and autolysin. Finally, we used a murine model to demonstrate that TRQ efficiently reduces bacterial virulence. Altogether, we have proved TRQ formula to be an effective agent against S. aureus infections.